Beyond Relational Demography: Time and the Effects of Surface- and Deep-Level Diversity on Work Group Cohesion - Harrison, David A.; Price, Kenneth H.; Bell, Myrtle P. (Academy of Management Journal, 1998)
We examined the impact of surface-level (demographic) and deep-level (attitudinal) diversity on group social integration. As hypothesized, the length of time group members worked together weakened the effects of surface-level diversity and strengthened the effects of deep-level diversity as group members bad the opportunity to engage in meaningful interactions.